Learning through observing: Effects of modeling truth‐ and lie‐telling on children's honesty. Issue 1 (26th July 2019) - Engarhos, Paraskevi; Shohoudi, Azadeh; Crossman, Angela; Talwar, Victoria
Abstract: The current study examined the influence of observing another's lie‐ or truth‐telling – and its consequences – on children's own honesty about a transgression. Children ( N  = 224, 5–8 years of age) observed an experimenter (E) tell the truth or lie about a minor transgression in one of five conditions: (a) Truth‐Positive Outcome – E told the truth with a positive outcome; (b) Truth‐Negative Outcome – E told the truth with a negative outcome; (c) Lie‐Positive Outcome – E lied with a positive outcome; (d) Lie‐Negative Outcome – E lied with a negative outcome; (e) Control – E did not tell a lie or tell the truth. Later, to examine children's truth‐ or lie‐telling behavior, children participated in a temptation resistance paradigm where they were told not to peek at a trivia question answer. They either peeked or not, and subsequently lied or told the truth about that behavior. Additionally, children were asked to give moral evaluations of different truth‐ and lie‐telling vignettes. Overall, 85% of children lied. Children were less likely to lie about their own transgression in the TRP when they had previously witnessed the experimenter tell the truth with a positive outcome or tell a lie with a negative outcome. Abstract : Children observed a confederate lie or tell the truth about a transgression with resulting positive or negative consequences. Children who witnessed the confederate tell the truth with a positive outcome (Lie‐positive condition) or tell a lie with a negative outcome (Lie‐negative condition) were later less likely to lie about their own transgression.